Population Genomic Analysis of Diploid-Autopolyploid Species - Bohutínská, Magdalena; Vlček, Jakub; Monnahan, Patrick; Kolář, Filip (Methods in molecular biology (Clifton, N.J.), 2023)
This chapter outlines an empirical analysis of genome-wide single-nucleotide polymorphism (SNP) variation and its underlying drivers among multiple natural populations within a diploid-autopolyploid species. The aim is to reconstruct the genetic structure among natural populations of varying ploidy and infer footprints of selection in these populations, framed around specific questions that are typically encountered when analyzing a mixed-ploidy data set,e.g., addressing the relevance of natural whole-genome duplication for speciation and adaptation. We briefly review the options for the analysis of polyploid population genomic data involving variant calling, population structure, demographic history inference, and selection scanning approaches. Further, we provide suggestions for methods and associated software, possible caveats, and examples of their application to mixed-ploidy and autopolyploid data sets.
Keywords: Selection scans; aklimatizace; Arabidopsis; Genetic variation; metagenomika; genomika; Ploidies; Autopolyploidy; ploidie; Acclimatization; Metagenomics; Genomics; Population differentiation; Diploidy; diploidie